2018
DOI: 10.15561/20755279.2018.0605
|View full text |Cite
|
Sign up to set email alerts
|

Effects of royal jelly and honey mixture on some hormones in young males performing maximal strength workout

Abstract: Background and Study Aim: Among products used as ergogenic substances by sportsmen, royal jelly and honey have attracted attention in recent years. This study was carried out to determine the effect of royal-jelly and honey mixture on weight lifting performances and some hormone test of athletes. Material and Methods: Randomly selected healthy 29 athletes, aged between 20 and 25 years, were divided into two groups. Placebo (corn starch) was given to the Control Group and 5 grams of royal jelly + 45 grams of ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The reduction of CRP can be attributed to the effect of royal jelly in addition to exercise. Royal jelly contains important compounds such as proteins, sugars, lipids, amino acids, vitamins and minerals; It also has a wide range of medicinal functions such as antioxidant, anti-edematous, antimicrobial, anti-allergic and anti-tumor properties and protective effects on immune, inflammatory and nervous systems (21). Nora et al (2020) reported a significant decrease in CRP as a result of eight weeks of endurance training and consumption of royal jelly (100 mg/kg) in the muscle tissue of rats with Alzheimer's disease (22).…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of CRP can be attributed to the effect of royal jelly in addition to exercise. Royal jelly contains important compounds such as proteins, sugars, lipids, amino acids, vitamins and minerals; It also has a wide range of medicinal functions such as antioxidant, anti-edematous, antimicrobial, anti-allergic and anti-tumor properties and protective effects on immune, inflammatory and nervous systems (21). Nora et al (2020) reported a significant decrease in CRP as a result of eight weeks of endurance training and consumption of royal jelly (100 mg/kg) in the muscle tissue of rats with Alzheimer's disease (22).…”
Section: Discussionmentioning
confidence: 99%
“…The researchers noted that there is a need for a more detailed study of apitherapy and the impact on human health [33]. The study of the role of apitherapy for human health shows that among the products used by athletes as ergogenic substances, in recent years, attention is drawn to royal jelly and honey [34].…”
Section: Discussionmentioning
confidence: 99%
“…In fact, RJ has an insulin-like activity—an insulin-like peptide had been purified from RJ and it is similar to insulin of vertebrates in solubility, chromatographic, immunological, and biological characteristics [84]. Administration of RJ to healthy athletes significantly decreased their insulin and increased thyroxine (T4) hormone levels in plasma [85]. In line with this, healthy adults who consumed a single oral dose of RJ (20 g) immediately before oral glucose tolerance test showed significantly reduced glucose level [86].…”
Section: Rj Might Enhance Longevity In Humans By Promoting Generalmentioning
confidence: 99%